Kegiatan Seni Melipat Kertas melalui Youtube untuk Meningkatkan Keterampilan Motorik Halus Anak Usia Dini - Agustin, Susi; Hasanah, Hisbiyatul; Pradana, Pascalian Hadi (Jurnal Simki Pedagogia, 2024)
Stimulating early childhood through artistic development and fun play activities has an impact on the development of every aspect of a child's development. This research aims to find out that paper folding art activities via YouTube can improve children's fine motor skills. Researchers used research in the form of class activities with a total of 15 children. Observation of child development uses a checklist form which contains the child's development from not yet developing to developing very well. The conclusion obtained is that paper folding art activities via YouTube can improve children's fine motor skills. Class action research in cycle I reached 66.67%, and in cycle II, these results could increase by 87.62%. This is due to the fact that paper folding using YouTube videos can attract children's attention, make learning more fun, and improve their motor skills.